Globalisation, development, and child rights - Satyarthi, Kailash; Zutshi, Bupinder (Delhi Shipra, 2006)
Contributed articles presented earlier at a workshop.
Keywords: Child labor -- India -- Congresses; Children's rights -- India -- Congresses